The Impact of Telemedicine on Rheumatology Care - Tang, Wei; Inzerillo, Sean; Weiner, Julia; Khalili, Leila; Barasch, Julia; Gartshteyn, Yevgeniya; Dall'Era, Maria; Aranow, Cynthia; Mackay, Meggan; Askanase, Anca (Frontiers in Medicine, 2022)
Background The pandemic disrupted the care of patients with rheumatic diseases; difficulties in access to care and its psychological impact affected quality of life. Telemedicine as an alternative to traditional face-to-face office visits has the potential to mitigate this impact. Objective To evaluate patient and provider experience with telemedicine and its effect on care. Methods We surveyed patients with rheumatic diseases and their rheumatology providers. The surveys were conducted in 2020 and repeated in 2021. We assessed data on quality of care and health-related quality of life. Results 100 patients and 17 providers responded to the survey. Patients reported higher satisfaction with telemedicine in 2021 compared to 2020 (94% vs 84%), felt more comfortable with (96% vs 86%), expressed a stronger preference for (22% vs 16%), and higher intention to use telemedicine in the future (83% vs 77%); patients thought physicians were able to address their concerns. While providers’ satisfaction with telemedicine increased (18% to 76%), 14/17 providers believed that telemedicine visits were worse than in-person visits. There were no differences in annualized office visits and admissions. Mean EQ-5D score was 0.74, lower than general population (0.87) but equivalent to a subset of patients with SLE (0.74). Conclusion Our data showed a high level of satisfaction with telemedicine. The lower rheumatology provider satisfaction raises concern if telemedicine constitutes an acceptable alternative to in-person care. The stable number of office visits, admissions, and the similar quality of life to pre-pandemic level suggest effective management of rheumatic diseases using telemedicine/in-person hybrid care.